Studi Mikroskopis Fase-Fase Mitosis pada Sel Akar Bawang Merah (Allium cepa) sebagai Model Pembelajaran Biologi Sel - Margaretha Alesandria Natasya Weka; Feni Atika Tsuroyya; Septi Puspita Kurniawati; Azlinatul Lulu Kharolaini; Pramai Sheila Eka Khoireina; Liss Dyah Dewi Arini (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to observe the phases of mitosis in the meristem cells of shallot roots (Allium cepa) through microscopic observation as part of the Cell Biology learning model. Mitosis is an important part of the cell cycle that plays a role in growth, tissue repair, and asexual reproduction in organisms. A deep understanding of the mitosis process is an important foundation in various branches of biology, including genetics, biotechnology, and histology. Shallot roots were chosen because they have actively dividing meristem tissue at the root tip,as well as a large and transparent cell structure that facilitates the staining and observation process. Preparation was carried out by soaking the onion roots in a solution of acetic acid and alcohol for fixation,then staining with acetocarmine acid so that the chromosomes are clearly visible. The process of crushing the root tip and pressing it on a glass object (squash method) was used to expand the observation area. A light microscope with a magnification of 400x and 1000x was used to identify the division phases. Observation results show the presence of all phases of mitosis, namely prophase (nucleolus and nuclear membrane begin to disappear,chromosomes condense), metaphase (chromosomes line up at the equator), anaphase (chromatids separate to opposite poles), and telophase (nuclear membrane and two daughter cell nuclei re-form). Visual documentation in the form of microscopic photographs and descriptive tables clarify the identification of these phases, thus facilitating student understanding.From a pedagogical perspective, this microscopic practicum-based learning has been proven to improve students' observational skills, laboratory skills, and conceptual understanding of cell division. Students not only memorize theories, but directly experience the scientific process through exploration and discussion of observation results. Evaluation of learning outcomes is carried out through post-practicum quizzes and student worksheets, showing an increase in understanding scores of more than 30%.